2020
DOI: 10.3332/ecancer.2020.1154
|View full text |Cite
|
Sign up to set email alerts
|

The impact of monthly campaigns and other high-profile media coverage on public interest in 13 malignancies: a Google Trends analysis

Abstract: It is estimated that more than 600,000 people will die of cancer in the United States in 2020. Annual cancer diagnoses throughout the country are expected to rise in the coming years, which may further strain the American healthcare system. As such, it is vital that public health campaigns intended to reduce cancer morbidity and mortality are successful. Monthly cancer awareness campaigns have been used in the past to raise awareness and funding for various malignancies. One notable example is the ‘Pink Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…“When” and “where” the information is shared also play an important role. Cohen et al and Glynn et al both showed in their studies that cancer awareness months are effective in increasing Internet search traffic/public interest [ 22 , 23 ]. In addition to the proposed annual “Brachytherapy Day” on July 17 [ 9 ], we could also utilize brachytherapy’s versatility in treating various cancers (e.g., prostate cancer, cervical cancer, and breast cancer) and tie in with their respective awareness months, thus gaining multiple publicity opportunities every year.…”
Section: Discussionmentioning
confidence: 99%
“…“When” and “where” the information is shared also play an important role. Cohen et al and Glynn et al both showed in their studies that cancer awareness months are effective in increasing Internet search traffic/public interest [ 22 , 23 ]. In addition to the proposed annual “Brachytherapy Day” on July 17 [ 9 ], we could also utilize brachytherapy’s versatility in treating various cancers (e.g., prostate cancer, cervical cancer, and breast cancer) and tie in with their respective awareness months, thus gaining multiple publicity opportunities every year.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings finally demonstrated that the accessibility to healthcare service and logistics for screening program has been recognized as the most powerful factor for seasonality of cancer diagnosis rather than the multifactorial etiology. Seasonal variation of cancer detection is a surrogate maker of effective cancer screening program from the perspective of increasing screening efforts for cancer diagnosis 21–23 …”
Section: Discussionmentioning
confidence: 99%
“…To confirm the impact of the awareness months on public interest, we performed another analysis to estimate the difference in the mean weekly RSVs of the subjective and non-awareness months. As in a recent study 19 , the mean RSVs of January (CCAM, week 1st to 4th) and November (CCPAEM, week 45th to 48th) were compared to the mean RSVs for the rest of the year by the Kruskal–Wallis test. The threshold for statistical significance was defined as a p -value < 0.05, which indicated the level at which the slope differed from zero.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, since 2010, November is the cervical cancer prevention awareness enhancement month (CCPAEM) in Japan, which has been endorsed by CancerNet Japan 18 . Recently, several studies have reported the usefulness of measuring public attention toward malignant diseases during the Cancer Awareness Months by the method of Google Trend analysis 19 , 20 . However, impacts of those awareness campaigns on public interests has not been fully evaluated in Japan.…”
Section: Introductionmentioning
confidence: 99%